Analisis Efisiensi Kinerja Unit Usaha Syariah Di Indonesia Dengan Metode Data Envelopment Analysis Dan Rasio Eagles - Muhammad Fauzan Yasir Tsany; Purnama Putra; Mas Deden Tirtajaya (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
This research is motivated by global competition that occurs in economic life which requires every institution to determine the appropriate strategy from the point of view of Efficiency and Performance Levels. The purpose of this study is to measure the level of efficiency and performance of the Sharia Business Unit and to see the factors that affect the level of efficiency and performance of the Sharia Business Unit. The research method used in this research is descriptive quantitative using secondary data. Secondary data comes from the documents of Sharia Business Units included in the National Private Commercial Bank. DEA analysis is used to measure the level of efficiency by analyzing internal factors in the form of efficiency targets on total assets, third party funds, labor costs, total financing and revenue sharing, while the EAGLES analysis is used to measure performance which consists of earning ability, asset quality, growth rate, liquidity, equity and strategic management. The results of the analysis using the DEA approach can be seen that the Sharia Business Units in Indonesia have not reached the optimum level of efficiency, this is due to the target on the input variable consisting of total assets, third party funds and labor costs that are still experiencing waste and have not met the efficiency target, while the results of the EAGLES analysis show that the performance of the Sharia Business Unit is in a good performance condition to become an alternative choice for the community.